Anatomic and radiograph study of the persistence of Foramen of Huschke - Moreno, Rodrigo Costa; Chilvarquer, Israel; Hayek, Jorge E.; Seraidarian, Paulo Isaias [UNESP] (FapUNIFESP (SciELO), 2005)
Aim: the aim of this study is to assess and locate the Foramen of Huschke. Study design: anatomical. Material and Method: using contrast material like gutta-percha and barium sulfate, through extraoral radiographs, such as panoramic, submental vertex and corrected saggital linear Temporal Mandibular Joint tomograms in four skulls where we clinically checked the existence of foramen of Huschke. Results: The results proved that the foramen of Huschke can be observed in skulls submitted to contrast using radiographic techniques.
Keywords: Corrected sagittal linear temporal mandibular joint tomograph; Huschke's Foramen; Panoramic; Submental vertex; barium sulfate; contrast medium; gutta percha; adult; bone malformation; controlled study; human; human tissue; preschool child; radiography; skull; temporomandibular joint; tomography; Adult; Ear, Middle; Humans; Middle Aged; Radiography, Panoramic; Temporal Bone; Temporomandibular Joint; Tomography, X-Ray Computed